DYNAMICS OF THE CONTENTS OF THE MAIN ELEMENTS OF NUTRITION AND PRODUCTIVITY OF WINTER SOFT WHEAT DEPENDING ON THE PRIMARY METHOD OF TILLAGE - E. D. Krivosheeva; N. V. Nekhoroshova; A. A. Sukharev; G. V. Metlina (Зерновое хозяйство России)
The long-term trials in the southern part of theRostovregion showed that the primary method of tillage had a great effect on the dynamics of the contents of the main elements of nutrition and productivity of winter soft wheat. The experiments were started with 4 crop rotation sequences in 2007 on the fields of FSBSI ARRIGC after I.G. Kalinenko. The soil of the plot was ordinary carbonate loam black earth (chernozem). There were studied three methods of tillage, surface, subsoil and moldboard. There were analyzed the data of three year research of the dynamics of the contents of the main elements of nutrition (nitrate nitrogen, movable phosphorus, exchangeable potassium) in the layers of 0-10, 10-20, 20-30 cmduring the vegetation of the crop under the use of mentioned methods of tillage. There was no significant difference in the total contents of the main elements of nutrition in the layer 0-30 cmduring the vegetation of the crop. In the precise analysis of the soil layers it was found that under the surface tillage the contents of the movable forms of nitrogen and phosphorus was larger than under the subsoil and moldboard tillage. During the stage of head formation, the contents of nitrate nitrogen and phosphorus in the layer 0-20 cmunder the surface tillage was 55% and 16- 17% more than under the subsoil and moldboard tillage. The high supply of mineral nutrition, sufficient moisture and favorable temperature regime formed the maximum productivity of the crop (5.23 t/ha) under the surface tillage. During the years of study the larger contents of nitrate nitrogen and movable phosphorus was found in the layer of 0-20 cmunder the surface tillage and potassium under the use of moldboard tillage. Under the minimum tillage changeable potassium is accumulated in the top layer of soil, the subsoil and moldboard tillage promotes the process of mineralization of the whole arable layer and leads to a uniform accumulation of available potassium in the top layer of soil. The economic and bioenergetics assessment of the efficiency of the effect of the tillage methods on productivity of winter soft wheat showed that due to the decrease of the expenditures and the increase of crop productivity under the surface tillage the profitability of the winter wheat cultivation was 107.7-192.8%, the coefficient of the energetic efficiency (CEE) was 2.7-5.5% depending on the amount of productivity. Under the moldboard tillage the profitability of the crop ranged from 52.5 to 163.5%, the energetic efficiency (CEE) was 1.8-4.6%; they were 70.0-172.4% and 2.3-5.1% respectively under the subsoil tillage.